The impact of administrative transaction costs in the EU emissions trading system. (3rd April 2017) - Heindl, Peter
Abstract : This article empirically investigates the impact of transaction costs for monitoring, reporting, and verification (MRV) of emissions on companies regulated by the EU Emissions Trading System (EU ETS) in Germany. Based on a unique panel dataset, we investigate if MRV costs are dependent on the amount of annual emissions of regulated companies and if there are differences in transaction costs between economic sectors. The results indicate that administrative costs are dependent on the amount of annual emissions for larger companies, which has implications for the economic efficiency of the EU ETS. The most important finding, however, is that there are significant differences in MRV transaction costs dependent on the type and size of companies. This implies the existence of considerable economies of scale. Overall, the EU ETS could benefit from reforms by means of a push towards upstream regulation as this would likely increase administrative efficiency. Policy relevance statement Transaction costs are, among other things, an important aspect of market-based climate policy design. A policy instrument with low transaction costs is preferred over instruments with larger transaction costs under equal conditions. This is occasionally referred to as administrative efficiency, and its importance was acknowledged in directive 2009/29/EC of the European Commission. Thoughtful empirical examination of transaction costs is essential in order to inform about the extent and impact of these costs. This article provides an analysis of transaction costs for monitoring, reporting, and verification (MRV) of emissions in the EU ETS. It is shown that administrative costs will likely have negative effects on the cost efficiency of the EU ETS. However, the most relevant finding is that small companies (<250 employees) or firms emitting small amounts of carbon dioxide per year face far higher average transaction costs compared with larger firms or emitters. Thus, there is a tendency for the EU ETS to cause MRV transaction costs that are disadvantageous for small companies. A regulation that is more upstream-oriented could mitigate this negative effect to some extent. The EU ETS could initiate a reform that is targeted on putting a price on the carbon content of fossil fuels instead of directly regulating emissions in a so-called 'end-of-the-pipe' way at the installation level.